Temuan insidental dense bone island pada radiograf panoramik - Anak Agung Istri Agung Feranasari; Ria Noerianingsih Firman; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: The aim of this study is to increase knowledge about Dense Bone Island diagnosis and differential diagnosis as well as emphasize on radiographic characteristics of this lesion. Case Report: A male 24 years came to the Dentomaxillofacial Radiology Installation, Faculty of Dentistry Dental Hospital Universitas Padjajaran referred for radiographic examination from the Periodontics Department. The patient will be paired dental implants in the second premolar in the right mandible. Patients had no inflammation and pain. The patient then were take radiography examinations as indicated dental implant, that were periapical, panoramic and CBCT, then one of the radiographic examination was done, the panoramic which shows radiopaque, well-defined, rounded irregularly shaped lesion with a diameter of approximately 6 mm, which is located around apical first premolar teeth in the right mandible. Mandible first premolar is still vital. Conclusion: Dense bone Island is an increased bone density that occurs in the maxilla or mandible especially around the root of a tooth, and is often asymptomatic. Cases that occur in these patients have no clinical complaints either before or after the installation of dental implant.